Pelatihan Microsoft Word Dasar Untuk Perangkat Desa Gelang Kecamatan Sumber Baru Kabupaten Jember - Ginanjar Abdurrahman (Journal of Community Development, 2021)
In community service, especially village administration, ideally, village officials have essential Microsoft word competencies. However, from the report from the village apparatus of Gelang, only one person who mastered the basic Microsoft word was not comprehensive. Basic Microsoft word skills are considered necessary by the village apparatus of Gelang. This material chose because this material has not been mastered and deemed to be most often needed to handle the Gelang village office's administration, so it is necessary to hold basic Microsoft word training activities for the village apparatus of Gelang. This activity was born on September 7, 2016, introducing the presenter followed by a pre-test to determine the participants' initial abilities. After that, the presentation of material about basic Microsoft word accompanied by mentoring, practice, discussion and ended with a post-test continued with the material's production. The activity evaluation data shows that the participant's post-test scores' lowest score wa perfect compared to the participant's pre-test scores. The lowest score for the participant's post-test was 75, and the highest score for the participant was 90 compared to the pre-test score with the highest score only reaching 60/ Thus, it can say that there was a significant increase in the score.